THE INFLUENCE OF QUALITY PRODUCTS AND QUALITY OF CUSTOMER LOYALTY IN CIGARETTE CLASS MILD(CASE STUDIES IN PT.NIAGA NUSAABADI BANDAR LAMPUNG) - Farida Efriyanti; Ferdy Rahman (International Conference On Law, Business and Governance (ICon-LBG), 2016)
This research is motivated a condition that is now increasingly fast-moving business where competition is more advanced in the field of cigarettes. Integration thus a need to have a marketing strategy in order to maintain and towards higher market share. As for the issue of this study is "What are the factors of product quality, service quality, positive effect on consumer loyalty Class Mild cigarette?". The purpose of this study was to analyze the effect of each - each variable, the quality of the product (X1), quality of service (X2), customer loyalty (Y). In this study, the data collected through questionnaires to 70 respondents who consume Class Mild cigarettes. Quantitative analysis includes the validity and reliability, test analisisi multiple linear regression, hypothesis testing through F test and t test and determinisasi coefficient (R2). Data that has met the test of validity, reliability test, test analisisi multiple linear regression, hypothesis testing through F test and t test and determinisasi coefficient (R2) is processed to produce a regression equation as follows:Y = 20.521 + 0.568 X1 + 0.405 X2. The results of the analysis found that both factors of product quality, service quality, has a positive and significant impact on customer loyalty. Testing the hypothesis that to use it t test showed that two independent variables studied was shown to significantly affect the dependent variable customer loyalty. Then through the F test can be seen that the variable product quality, service quality, significant effect together - together in customer loyalty. Calculation results obtained Rx, y = 0.649 and determination coefficient R²x, y = 0.649 or 64.90%. The magnitude of the coefficient of determination, giving the sense that the magnitude of change in consumer loyalty 64.90% variable is explained by the quality of product and quality of service while the remaining 35.10% is explained by other factors not authors carefully.